2022
DOI: 10.3390/polym14153131
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interfacial Adhesion on the Mechanical Behavior of Thin Metal/Polymer Laminate with Surface Roughness

Abstract: Metal/polymer laminate has versatile applications in industry due to the essential roles of its constituents in controlling its mechanical behavior. Therefore, efforts to enhance a laminate’s performance should target its mechanical behavior. One of the most influencing features of the mechanical behavior of this type of thin laminate is the interface layer properties. This study concentrates on the mechanical response of thin aluminum (Al) foil deposited on a polymer substrate by calibrating its interfacial l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Thermo-sealing of polymer films on paper substrate is a complex process that is influenced by different factors, e.g., polymer–paper compatibility, interfacial energy between both surfaces, and structural changes occurring during storage [ 59 ]. Thus, the analysis of the seal strength in the bilayer structures is of relevance to ensure the material’s functionality in food packaging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermo-sealing of polymer films on paper substrate is a complex process that is influenced by different factors, e.g., polymer–paper compatibility, interfacial energy between both surfaces, and structural changes occurring during storage [ 59 ]. Thus, the analysis of the seal strength in the bilayer structures is of relevance to ensure the material’s functionality in food packaging.…”
Section: Resultsmentioning
confidence: 99%
“…The authors showed that the PHB-based layer was also peeled off with torn paperboard fibers, up to the final failure of the PHB layer, suggesting that the interfacial adhesion also presented greater resistance to tear. Thermo-sealing of polymer films on paper substrate is a complex process that is influenced by different factors, e.g., polymer-paper compatibility, interfacial energy between both surfaces, and structural changes occurring during storage [59]. Thus, the analysis of the seal strength in the bilayer structures is of relevance to ensure the material's functionality in food packaging.…”
Section: Samplementioning
confidence: 99%